2019
DOI: 10.2147/idr.s204618
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sensitivity Pattern Of <em>Salmonella typhi</em> And Paratyphi A Isolates To Chloramphenicol And Other Anti-Typhoid Drugs: An In Vitro Study</p>

Abstract: PurposeTo investigate the antimicrobial sensitivity pattern of commonly prescribed antimicrobials (chloramphenicol, cefixime, ofloxacin, azithromycin, and ceftriaxone) against Salmonella enterica isolates.MethodsBlood culture positive isolates of S. typhi and S. paratyphi A (N = 251) received at Metropolis Healthcare Limited (Mumbai, India) from four zones of India (North, South, West, and East) between April and August 2018 were tested for antimicrobial susceptibility by E-test method. Based on the minimum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 56 publications
0
18
1
Order By: Relevance
“…17 While study of Patil and Mule they found S. typhi sensitive to Cefixime, Ceftriaxone, and Azithromycin and based on average Minimal Inhibitory Concentration and MIC breakpoints. 30 Through the experiment conducted on Rats by Qnais et al (2012) which found L. nobilis aqueous extract has antidiarrheal agent. 31 Study of Nafi s et al exhibited notable potency regarding antimicrobial activity of (EOs) from L. nobilis leaves had the highest activity against E. coli, with MIC: 22.2 mg/mL and IZ 9.00 mm.…”
Section: Resultsmentioning
confidence: 99%
“…17 While study of Patil and Mule they found S. typhi sensitive to Cefixime, Ceftriaxone, and Azithromycin and based on average Minimal Inhibitory Concentration and MIC breakpoints. 30 Through the experiment conducted on Rats by Qnais et al (2012) which found L. nobilis aqueous extract has antidiarrheal agent. 31 Study of Nafi s et al exhibited notable potency regarding antimicrobial activity of (EOs) from L. nobilis leaves had the highest activity against E. coli, with MIC: 22.2 mg/mL and IZ 9.00 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Non-susceptibility of Typhoidal Salmonella to first-line antimicrobials (chloramphenicol, co-trimoxazole and ampicillin) has decreased over time as also reported by other studies. 5,6,13,14 Hence routine surveillance of resistance determinants is essential to understand the comeback of first generation of antibiotics for the treatment of typhoid fever.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in India showed that all the typhoidal strains of Salmonella were sensitive to ceftriaxone and azithromycin. Ninety-four strains were also sensitive to chloramphenicol, and only 3.6% were sensitive to ofloxacin [17]. [18].…”
Section: Discussionmentioning
confidence: 99%